Isolation and characterization of polyphenols in natural honey for the treatment of human diseases - Mohd Hilmi, Abu Bakar; Fatima, Ibrahim Jibril; Lavaniya, Manivannan (2019)
Honey is a natural sweetener that is derived from the nectar, pollen, and resin of plants. It has been used as a folk medicine for decades. In addition to being an excellent therapeutic agent, honey possesses an unusually high nutritional content, thus generating interest among researchers. The major phytonutrients of honey are polyphenols. Polyphenols can be separated using high-performance liquid chromatography (HPLC) or liquid chromatography-mass spectrometry (LC-MS). Moreover, to separate the volatile compounds in honey, gas chromatography-mass spectrometry (GC-MS) may be used. Polyphenols have unique and complex structures that are mainly composed of flavonoids and phenolic acids, which confer significant antiviral, anti-inflammatory, antineoplastic, and antiulcer effects and can be used to treat chronic diseases, such as cardiovascular disease. The nature and variability of polyphenols in different honeys posed a challenge to investigations in previous years. Nevertheless, the significant role of honey as a natural therapy and its enrichment with natural substances have led to the continuous discovery of efficient, reliable, and rapid methods for the identification and quantification of novel bioactive compounds in honey. This current review highlights the above mentioned issues.